(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The educational system in Ecuador has undergone changes that have urgently transformed the face-to-face modality to the virtual one. This paper presents a study of three educational units in the city of Quito - Ecuador, the objective of this research is to detect the occupational stress suffered by physical education teachers in times of pandemic, an exploratory and descriptive study was conducted. The participants in the study included in the study were 175 teachers from three educational units, 57 teachers from the first UE, 76 teachers from the second UE and 42 teachers from the third UE (Educational Unit), of which there were 114 men and 61 women, to detect the levels of stress the Maslach Burnout Inventory (MBI) questionnaire was applied, which consists of 22 items in the form of statements, about the feelings and attitudes of teachers in their work and towards students, for which its function is to measure professional burnout. It also aims to measure the frequency and intensity with which the teacher suffers Burnout.